Assessing the Role of State and Local Public Health in Outreach and Enrollment for Expanded Coverage A Case Study on New Orleans, Louisiana - Williams, Malcolm V. (RAND Corporation, 2016)
Part of a series highlighting innovative models and best practices for leveraging local health departments' involvement in Patient Protection and Affordable Care Act outreach and enrollment, this report describes a case study on New Orleans, Louisiana, that captures nuanced differences in how health departments support these efforts, identifies facilitators and barriers to these approaches, and develop lessons learned from these activities.